1988
DOI: 10.2105/ajph.78.9.1175
|View full text |Cite
|
Sign up to set email alerts
|

Child care and children's illness.

Abstract: This paper uses nationally representative data from the Child Health Supplement of the 1981 National Health Interview Survey to test the hypothesis that the larger the groups in which children receive care, the more days per year they spend in bed due to illness. We estimate a model of annual bed days for children ages six months to two and one-half years old, and separately for children two and one-half to five years old. Our results show significantly higher numbers of bed days for children in day care cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 15 publications
0
11
0
3
Order By: Relevance
“…This observation is particularly impor tant because evidence suggests that frequent episodes (es pecially of otitis media) may adversely affect neurocognitive and language development [8] and lead to numerous medical and surgical treatments [9]. Several studies in Scandinavia [3,4,10] showed that the prevalence of abnormal tympanograms ranged from 5 to 8% in children at home or attending family day care, respectively, com pared to 24% in children attending DCCs.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is particularly impor tant because evidence suggests that frequent episodes (es pecially of otitis media) may adversely affect neurocognitive and language development [8] and lead to numerous medical and surgical treatments [9]. Several studies in Scandinavia [3,4,10] showed that the prevalence of abnormal tympanograms ranged from 5 to 8% in children at home or attending family day care, respectively, com pared to 24% in children attending DCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Eugenia Nandí-Lozano, M en C, (1) Luz Elena Espinosa, M en C, (2) Lucía Viñas-Flores, MC, (2) Carlos Avila-Figueroa, Dr en C. …”
Section: Infección Respiratoria Aguda En Niños Que Acuden a Un Centrounclassified
“…Se tomaron cultivos nasofaríngeos con una prevalencia de colonización para S. pneumoniae de 20 L as condiciones económicas de las familias que residen en zonas urbanas han provocado que ambos padres trabajen, factor asociado con el aumento de los niños en las guarderías. [1][2][3] El fenómeno, si bien favorece su socialización y el desarrollo temprano de habilidades, la interacción diaria con otros niños facilita la diseminación de enfermedades infecciosas.…”
Section: Introductionunclassified
“…One study, for example, showed that children attending day-care centers suffered more illnesses than children at home. 18 Infectious diseases in crowded day-care centers may result from a synergistic effect of increased contact and poor ventilation, resulting in inadequate removal ofmicroorganisms. Ifthere is a link between these and other health effects and ventilation characteristics, criteria for day-care ventilation and building use should be adjusted.…”
Section: Levelsmentioning
confidence: 99%